Antifungal Combination Eye Drops for Fungal Keratitis Treatment - Victoria Díaz-Tomé; Carlos Bendicho-Lavilla; Xurxo García-Otero; Rubén Varela-Fernández; Manuel Martín-Pastor; José Llovo-Taboada; Pilar Alonso-Alonso; Pablo Aguiar; Miguel González-Barcia; Anxo Fernández-Ferreiro; Francisco J. Otero-Espinar (MDPI AG, 2022)
Fungal keratitis (FK) is a corneal mycotic infection that can lead to vision loss. Furthermore, the severity of FK is aggravated by the emergence of resistant fungal species. There is currently only one FDA-approved formulation for FK treatment forcing hospital pharmacy departments to reformulate intravenous drug preparations with unknown ocular bioavailability and toxicity. In the present study, natamycin/voriconazole formulations were developed and characterized to improve natamycin solubility, permanence, and safety. The solubility of natamycin was studied in the presence of two cyclodextrins: HPβCD and HPγCD. The HPβCD was chosen based on the solubility results. Natamycin/cyclodextrin (HPβCD) inclusion complexes characterization and a competition study between natamycin and voriconazole were conducted by NMR (Nuclear Magnetic Resonance). Based on these results, several eye drops with different polymer compositions were developed and subsequently characterized. Permeability studies suggested that the formulations improved the passage of natamycin through the cornea compared to the commercial formulation Natacyn®. The ocular safety of the formulations was determined by BCOP and HET-CAM. The antifungal activity assay demonstrated the ability of our formulations to inhibit the in vitro growth of different fungal species. All these results concluded that the formulations developed in the present study could significantly improve the treatment of FK.